2020
DOI: 10.5433/1679-0359.2020v41n1p145
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and intercurrence of reproductive pathogens in cattle from family farms in North of Minas Gerais, Brazil

Abstract: The aims of the present study were: to estimate the seroprevalence of Bluetongue vírus (BTV), bovine alphaherpesvirus 1 (BoHV-1), bovine viral diarrhea virus (BVDV), Brucella abortus and Leptospira spp. in cattle from family farms in North of Minas Gerais; to determine the intercurrence and association among these pathogens; and to assess the possible associated factors to seropositive herds and animals. For this, 476 cows from 46 farms were sampled and evaluated serologically. The seroprevalence in herds and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…has shown high seroprevalence, which needs control measures to reduce the economic loss related to these zoonoses. The results of this study showed a seroprevalence of 76.1% for Leptospira spp., mainly associated with abortions in cattle evaluated of the 46 farms; therefore, the economy of farms is affected and the risk of transmission in humans is increased by contact with livestock, which has been commonly associated with an increased risk (HAAS et al 2020).…”
Section: Impact On Human Healthmentioning
confidence: 99%
“…has shown high seroprevalence, which needs control measures to reduce the economic loss related to these zoonoses. The results of this study showed a seroprevalence of 76.1% for Leptospira spp., mainly associated with abortions in cattle evaluated of the 46 farms; therefore, the economy of farms is affected and the risk of transmission in humans is increased by contact with livestock, which has been commonly associated with an increased risk (HAAS et al 2020).…”
Section: Impact On Human Healthmentioning
confidence: 99%
“…A lista nacional de doenças notificáveis de pequenos ruminantes é subdividida em quatro categorias: Caprinos (Capra hircus) e ovinos (Ovis aries) são suscetíveis a várias das doenças listadas (BRASIL, 2013;TORRES, 2016;OIE, 2021a;QUINN et al, 2019;RADOSTITS et al, 2007;RIET-CORREA et al, 2001) e saber quais estão ocorrendo em nosso rebanho e suas magnitudes são fundamentais para o completo entendimento da situação sanitária da caprinovinocultura nacional e o estabelecimento de medidas de defesa animal. Neste sentido, levantamentos epidemiológicos abrangentes permitem revelar o panorama sanitário e propiciam um diagnóstico situacional sanitário global, além de trazer novas informações e promover conhecimento integrado e visão holística sobre saúde animal (CANDELA et al, 2009;HAAS et al, 2020;NIKBAKHT et al, 2015).…”
Section: O Introduçãounclassified
“…A. Dias et al, 2008;M. S. Lima, Nogueira, Okuda, Stefano, & Pituco, 2011;Oliveira, Lorenzetti, Alfieri, & Lisbôa, 2015; N. P. C. Bezerra, Bezerra, Santos, Pereira, & Silva, 2019;Haas et al, 2020). The form of presentation and severity of infections and their pathogenesis varies according to BoAHV1 virulence, in addition to the fact that the agent is able to establish latency, contributing to the maintenance of BoAHV1 infection in the herd through asymptomatic animals that spread the virus in healthy hosts (Biswas, Bandyopadhyay, Dimri, & Patra, 2013).…”
Section: Introductionmentioning
confidence: 99%